FUNCTIONAL STATE MONITORING FOR SAMBO WRESTLERS IN ANNUAL TRAINING CYCLE - Maltsev, G.S.; Stepanov, M.Y.; Zekrin, A.F.; Chernova, G.M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze benefits of the traditional and modular training systems using the sambo wrestlers’ functional fitness testing and management toolkit. Methods and structure of the study. We used the following methods and instrumental test systems in the study: analysis of the relevant theoretical and practical literature; training experiment; mathematical statistical data processing toolkit; and functional fitness tests by computerized Simona 111 Integrated Test and Monitoring System. The study was run at Znezhinka Winter Sports Training Center and Judo and Sambo Sports Club in Tchaikovsky in March 2019 through February 2020 (annual training cycle). We sampled for the study the 18-23 year-old sambo elite (n=30) with Candidate Masters and Master of Sports qualifications and split them up into Control and Experimental Group of 15 people each. Results and Conclusion. The functionality progress profiles obtained using Simona 111 Integrated Test and Monitoring System showed meaningful benefits of the Experimental Group training system scheduled on a modular basis versus the traditional Control Group system to make the Experimental Group highly fit for the major event – as verified by the actual competitive accomplishments of the Experimental Group in the top-ranking event of the season. This evidence gives us the grounds to recommend the modular training schedule for the junior elite athletes’ training systems.